2018
DOI: 10.26687/archnet-ijar.v12i3.1655
|View full text |Cite
|
Sign up to set email alerts
|

History Matters: The Origins of Biophilic Design of Innovative Learning Spaces in Traditional Architecture

Abstract: Recent empirical studies have shown a positive correlation between nature, the built environment and creativity in the human brain. During the medieval Islamic Golden Era, higher education buildings of non-medical ‘madrasa’ and medical ‘bimaristan’ institutions applied specific techniques and strategies so that human intellectual curiosity could flourish through direct and indirect contact with nature. In contrast, the architecture of modern universities has lessened students’ multisensory focus and engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…A considerable number of studies have confirmed the restorative role of natural environments in learning spaces through qualitative or quantitative analyses. These studies have shown that natural environments can improve students' concentration and learning abilities, and even reduce stress and fatigue [55][56][57]. There are studies on large and small indoor plants [58,59], as well as those on vertical greening [60], green walls, and nature posters [61].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of studies have confirmed the restorative role of natural environments in learning spaces through qualitative or quantitative analyses. These studies have shown that natural environments can improve students' concentration and learning abilities, and even reduce stress and fatigue [55][56][57]. There are studies on large and small indoor plants [58,59], as well as those on vertical greening [60], green walls, and nature posters [61].…”
Section: Discussionmentioning
confidence: 99%
“…Biophilia, a relatively new concept of bringing nature into homes and public spaces, can be found even in the earliest times of architecture (Abdelaal & Soebarto , 2018;Ramzy, 2015;Tereci, 2020). The number of scientific works searching for biophilic principles in traditional houses is limited compared to biophilia and monumental architecture research.…”
Section: Traditional Residential Buildings and Well-beingmentioning
confidence: 99%
“…There are many examples of the "Madrassa" in many countries, one of the best examples in Egypt is Sultan Hassan representing madrassa-mosque in Cairo built-in 1363 AC during the Mamluk Bahri period. This building incorporated many Biophilic Design patterns: order and complexity, change and metaphor of biomorphic forms, prospect and refuge, enticement, and risk and peril [14]. This research starts by explaining the evolution of biophilia and biophilic design, it continues by analyzing biophilic design in a new educational building influenced by Islamic architecture.…”
Section: Sense Of Place Vernacular Designmentioning
confidence: 99%